IMPLEMENTASI PERATURAN MENTERI PERTANIAN NOMOR 49 TAHUN 2020 TENTANG ALOKASI DAN HARGA ECERAN TERTINGGI PUPUK BERSUBSIDI SEKTOR PERTANIAN TAHUN ANGGARAN 2021 DI KABUPATEN PANDEGLANG(STUDI PADA KECAMATAN MANDALAWANGI) - Ersa Fikriya; Nopi Andayani (LPPM STIA Banten, 2022)
Subsidized fertilizer is one of the government programs in the agricultural sector to facilitate farmers in meeting fertilizer needs. The problems in this study regarding the distribution of subsidized fertilizers include: (1). The flow of fertilizer distribution is convoluted (2). The occurrence of delays in the delivery of fertilizer atthe time of planting harvest (3). The amount of subsidized fertilizer supply is small, only based on data on food crops. (4). Fertilizer prices that pass the Highest Retail Price (HET).The purpose of this research is to find out the implementation of Ministerial Regulation Number 49 of 2020 concerning Allocation and Determination of the Highest Retail Price in Pandeglang Regency (Study in Mandalawangi District). The method used in this research is purposive sampling. Based on the results of the study, it was found that the distribution of subsidized fertilizers has not been running as it should.The method used in this research is purposive sampling. Based on the results of the study, it was found that the distribution of subsidized fertilizers has not been running as it should. The size and objectives of this policy have not been achieved due to the lack of socialization regarding the subsidized fertilizer program which has led to blind knowledge of farmers regarding the amount of allocation and determination of HET that will apply in 2021It is seen that the social, economic and political conditions in the Mandalawangi District are supportive, but the social conditions of farmers who are still conservative are a little difficult to achieve the goals of thesubsidized fertilizer program.Suggestionss: there needs to be more supervision on distribution in order to avoid trade monopoly and provide understanding to farmer groups regarding the applicable regulations.